The Bible's yes to same-sex marriage : an evangelical's change of heart - Achtemeier, Mark, 1955- (Louisville, KY : Westminster John Knox Press, 2014)
In the early 2000's, Mark Achtemeier embarked on a personal journey with the Bible that led him from being a conservative, evangelical opponent of gay rights to an outspoken activist for gay marriage and a fully inclusive church. In "The Bible's Yes to Same-Sex Marriage," Achtemeier shares what led to his change of heart.
The harvest of despair: Why traditional condemnations of gay relationships can't be right -- Jesus and the law: How Biblical fragments can lead us astray -- With all your mind: Reading the Bible faithfully and responsibly -- "This is my body, given for you": God's plan for love, marriage and sexuality -- Special blessings: Why gay people have an honored place in God's heart -- Reclaiming the witnesses 1: Making sense of the Old Testament fragments -- Reclaiming the witnesses 2: Making sense of the New Testament fragments -- Testing the spirits: How do we know we're on the right track? -- The word of life: Biblical teaching for the real world.
Includes bibliographical references.
Keywords: Same-sex marriage -- Religious aspects -- Christianity; Sex -- Biblical teaching; Homosexuality -- Biblical teaching; Marriage -- Biblical teaching